Initial surgical management of a gunshot wound to the lower face – a stepwise approach. (April 2013) - Collin, John; Revington, Peter; Sisson, Richard; Thomas, Steven
Facial gunshot wounds are rarely encountered in the UK, but not to such an extent that emergency departments should not be prepared to deal with them. We describe the management of a self-inflicted shotgun wound to the lower face using a step-wise approach. The primary reconstruction of such injuries should be performed soon after stabilisation of the patient. Simple yet careful surgical techniques are often effective in cases of severe facial trauma that might initially appear to require tissue transfer techniques, as soft tissue loss is often less than initially estimated. Preservation and closure of remaining tissue should aim to reconstruct oro-facial units while leaving options for more advanced reconstructive techniques open for future procedures if necessary.